GROWING IMPORTANCE OF SMALL GREEN BUSINESS PLAN AND THEORETICAL ANALYSIS (Intent Research Scientific Journal, 2023)
This article analyzes the importance of small business development and marketing policies with ecological net benefits, not just profit for humans.